Early Ultrasound Response and Progressive Transmural Remission After Treatment With Ustekinumab in Crohn's Disease - Kucharzik, Torsten; Wilkens, Rune; D'Agostino, Maria-Antonietta; Maconi, Giovanni; Le Bars, Manuela; Lahaye, Marjolein; Bravatà, Ivana; Nazar, Maciej; Ni, Lioudmila; Ercole, Elena; Allocca, Mariangela; Machková, Naděžda; et al. (Clinical gastroenterology and hepatology, 2023)
BACKGROUND & AIMS: In this STARDUST substudy, the effect of ustekinumab on transmural bowel inflammation was assessed in adults with moderate-to-severe Crohn's disease (CD) by using intestinal ultrasound (IUS), a noninvasive imaging procedure. METHODS: STARDUST was an international, multicenter, phase 3b, interventional, randomized controlled trial specifically designed to compare treat-to-target and standard-of-care treatment strategies in ustekinumab-treated CD patients. In this substudy, the most affected bowel segment at baseline by IUS was used for all analyses. Key IUS endpoints (centrally read, parameter-blinded) were IUS response, transmural remission, bowel wall thickness (BWT), blood flow, bowel wall stratification, and inflammatory fat. RESULTS: Seventy-seven patients were evaluated. IUS response could be determined 4 weeks after treatment initiation, with progressive improvement through week 48. IUS response and transmural remission rates at week 48 were 46.3% and 24.1%, respectively. IUS response, transmural remission, BWT, and blood flow normalization rates were more pronounced in the colon and biologic-naive patients. Fair/moderate reliability (κ = 0.21-0.51) was observed between week 4 IUS response and week 48 overall endoscopic response and fecal calprotectin/complete biomarker outcomes. Endoscopy and IUS baseline agreement was >90% in determining the terminal ileum as the most affected bowel segment. IUS response absence at week 4 was associated with no endoscopic response (based on the simplified endoscopic score for Crohn's disease terminal ileum subscore) at week 48 (negative predictive value = 73%). CONCLUSIONS: In this first international, multicenter, interventional study, IUS showed that ustekinumab-treated CD patients achieved progressive IUS response (46.3%) and transmural remission (24.1%) through week 48, with a more robust response in the colon and biologic-naive patients. CLINICALTRIALS: gov number: NCT03107793.
Keywords: dospělí; biologické přípravky; kolon; Crohn’s Disease; Biological Products; Transmural Remission; Adult; výsledek terapie; Ustekinumab; STARDUST; Reproducibility of Results; Colon; lidé; Intestinal Ultrasound; Treatment Outcome; reprodukovatelnost výsledků; Crohn Disease; Remission Induction; indukce remise; Crohnova nemoc; ustekinumab; Humans